Human Robot Interaction in the Application of EEG Controlling Robots - Mohamed Alseddiqi; Anwar AL-Mofleh; Mohamed AlMahmood; Ammar Alzaidi (International Journal of Engineering and Management Research, 2023)
In order to control a robot precisely, this essay highlights the growing need for better communication tools between humans and machines. The best method of communication between them is a brain-computer interface (BCI), particularly for the treatment of persons with disabilities and the completion of complex activities like surgery, rehabilitation, and procedures, among other things. The purpose of the survey was to measure public perceptions of and awareness of human-robot interaction (HRI) in the context of brain-computer interfacing (BCI).